1976
DOI: 10.1139/v76-242
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of bird's nest fungi. Part 5. The isolation of 1-hydroxy-6-methyl-8-hydroxymethylxanthone, a new xanthone, from Cyathus intermedius. Synthesis via photoenolisation

Abstract: The structure of 1-hydroxy-6-methyl-8-hydroxymethylxanthone, a new xanthone isolated from the culture broth of Cyathus intermedius, has been confirmed by synthesis. Regioselective hydroxylation of the 8-methyl of 1-hydroxy-6,8-dimethylxanthone was achieved via the peroxide formed by reaction of oxygen with the photoenol, and also via bromination of the photoenol. Extraction of the mycelia of C. intermedius yielded ergosterol and D-mannitol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…1), the key correlations were between H‐13 and H‐OCH 3 at C‐12, between H‐15 and H‐18 and between H‐16 and H‐17, which suggested that H‐15 and H‐16 had the same orientation. Comparing with the NMR data for the known xanthone and sterigmatocystin,13, 14 the NMR data of the A and B rings were almost the same as that part of asperxanthon, but the data for the C and D rings were different. The key correlation was a cross‐peak of the NOESY in the C ring, which was between the aromatic proton (δ 6.68) and the methoxy proton (δ 3.95), which excludes the structure 1 ′ which can arise in the biosynthesis route of xanthones (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…1), the key correlations were between H‐13 and H‐OCH 3 at C‐12, between H‐15 and H‐18 and between H‐16 and H‐17, which suggested that H‐15 and H‐16 had the same orientation. Comparing with the NMR data for the known xanthone and sterigmatocystin,13, 14 the NMR data of the A and B rings were almost the same as that part of asperxanthon, but the data for the C and D rings were different. The key correlation was a cross‐peak of the NOESY in the C ring, which was between the aromatic proton (δ 6.68) and the methoxy proton (δ 3.95), which excludes the structure 1 ′ which can arise in the biosynthesis route of xanthones (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…The scaled-up fermentation of the fungal strain RKDO 785 allowed us to purify and identify three metabolites ( C1, C2 , and C9 ) by interpretation of 1D and 2D NMR experiments and comparison with literature data ( Figure 6 ). Compound C1 exhibited the pseudomolecular ion [M + H] + m/z 257.0809 (calculated for C 15 H 12 O 4 + , 257.0808), and together with the observed NMR data, identified C1 as the known metabolite 1-hydroxy-6-methyl-8-hydroxymethylxanthone (Ayer and Taylor 1976 ). In a similar manner, HRMS of compound C2 supported a molecular formula C 15 H 10 O 4 ([M–H] – 253.0498, Δ −3.1ppm) and the 1 H NMR data were in agreement with chrysophanol ( C2 ) (Agarwal et al 2000 ).…”
Section: Resultsmentioning
confidence: 96%
“…All of these structurally similar molecules failed to produce notable antimicrobial activities; however, 1-hydroxy-6-methyl-8-hydroxymethylxanthone was found to be cytotoxic in each of the cell lines tested, while chrysophanol bianthrone was found to have selective toxicity against the HTB-26 breast cancer cell line. The xanthone metabolite 1-hydroxy-6-methyl-8-hydroxymethylxanthone was first isolated from the basidiomycete Cyathus intermedius (Ayer and Taylor 1976 ); however the production has been reported from ascomycetes from various orders including the Eurotiales, Pleosporales, Pezizales and the Sordariales (Hein et al 1998 ; Höller et al 2000 ; Pockrandt et al 2012 ; Shen et al 2012 ). The anthraquinone metabolite, chyrsophanol is one of the few polyketide natural products that occur in a broad range of eukaryotes as well as a few prokaryotes (Bringmann et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fractions 2 and 3 (eluted with 100% CH2Cl2) contained compounds 1 ( ; other characteristics of 2, including mp, IR, UV, MS, and 1 H NMR data, have been reported previously. 8 (*These assignments may be interchanged. )…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] On the basis of 1 H NMR, 13 C NMR, selective INEPT, and MS data, the second compound (C 15 H 12 O 4 ) was identified as 1-hydroxy-6-methyl-8-hydroxymethylxanthone (2), a metabolite previously reported from the fungus Cyathus intermedius. 8 Results from selective INEPT experiments on the methyl and methylene signals enabled confirmation of their relative positions on the xanthone nucleus. Com- parisons of the data for 2 with literature data 8 verified the structure.…”
mentioning
confidence: 98%